Panmixia in spiders (Mecaphesa celer, Thomisidae) despite fragmented habitat at Craters of the Moon in Idaho. (26th April 2022) - Peterson, Katie; Hendricks, Sarah; Hohenlohe, Paul; Parent, Christine E.
Abstract: A fragmented landscape, which contains a patchwork of vegetated hospitable areas and a barren intervening matrix, may reduce gene flow in a population and over time result in an increase in population structure. We tested this prediction in crab spiders ( Mecaphesa celer (Hentz, 1847)) inhabiting isolated habitat patches in the lava matrix of Craters of the Moon National Monument and Preserve, Idaho, USA. Using reduced‐representation genomic sequencing, we did not find evidence of population structure due to a reduction in gene flow among habitat patches. Instead, our results show strong evidence of panmixia likely due to abundant juvenile dispersal and possible connectivity to outer regions surrounding the lava flows despite the species' habitat specificity. Abstract : Results show strong evidence of panmixia likely due to abundant juvenile dispersal and possible connectivity to the outer lava flow region despite the species' habitat specificity. Not all fragmentation may cause a reduction in gene flow and an increase in population structure. Impact is dependent upon a combination of dispersal ability at different life stages, changes in resource availability, hospitability of the matrix, and/or length of time since fragmentation.